Controllable photon energy deposition efficiency in laser processing of fused silica by temporally shaped femtosecond pulse: Experimental and theoretical study. (August 2020) - Du, Kun; Li, Xiaowei; Zhang, Hao; Huang, Ji; Wang, Zhi; Yao, Zhulin; Lu, Yongfeng
Highlights: Photon energy deposition can be flexibly controlled by temporally shaped pulse. Plasma model considering ionization and its feedback explains the results reasonably. Parameters of temporally shaped pulse play a key role in photon energy deposition. Abstract: Photon energy deposition plays a crucial role in femtosecond laser irradiation followed by chemical etching processing, which is an emerging technique for the better control of micro/nano structures on fused silica. In this study, we have experimentally and theoretically studied the controllable photon energy deposition in laser irradiation of fused silica by temporally shaped femtosecond laser pulse trains. The experimental result shows that the photon energy deposition efficiency could be either reduced or enhanced by adjusting the total fluence of shaped pulse trains. Furthermore, the sub-pulse interval and intensity ratio of temporally shaped pulse trains were revealed to play a critical role in photon energy deposition. The corresponding experimental observations are qualitatively explained by a plasma model that considers the free electron generation processes and corresponding feedback on the photon energy deposition.